Preparation method of ultra-high-compaction lithium iron phosphate positive electrode material and lithium ion battery

Through the method of combining hollow microspheres with nanoparticles and in-situ composite of graphene, the problem of insufficient compaction density of lithium iron phosphate material is solved, and an efficient conductive network is built, which significantly improves the electrochemical performance.

CN119660704AActive Publication Date: 2025-03-21ZHUZHOU SHENGHUA TECH CO LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202510175182.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-21
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The compaction density of existing lithium iron phosphate materials is insufficient, resulting in long internal electron conduction and lithium ion transport distances, making it difficult to immerse the electrolyte, limiting the electrochemical properties of the material.

Method used

The combination of lithium iron phosphate particles of hollow microspheres and lithium iron phosphate nanoparticles is used to combine the in-situ composite of graphene and the surface carbon coating modification of sucrose to build an efficient conductive network.

Benefits of technology

It improves the compaction density and electrochemical performance of the material, reduces the obstacles and point contact effects of the electron transport interface, and achieves the efficient performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of an ultra-high-compaction lithium iron phosphate positive electrode material and a lithium ion battery, and relates to the technical field of lithium iron phosphate positive electrode materials. According to the preparation method, ferrous sulfate heptahydrate and a lithium phosphate hollow microsphere template are subjected to a reaction by adopting a solvothermal method to synthesize hollow lithium iron phosphate microspheres, then the reaction is directly continued on the basis to generate nanoscale lithium iron phosphate particles, and graphene is compounded in situ while the nanoscale lithium iron phosphate particles are generated; according to the preparation method, the hollow lithium iron phosphate microspheres and the nano-scale lithium iron phosphate particles are dispersed uniformly, graphene doping is completed, graphene is used as a conductive additive, sucrose is further used for surface carbon coating modification, so that a graphene-doped and carbon-coated synergistic efficient conductive network is constructed, and the graphene-doped and carbon-coated conductive network is prepared. The problems of electron transmission interface obstruction and point contact effect are solved, so that efficient transmission of electrons is realized, and the electrochemical performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium iron phosphate positive electrode materials, and in particular to a method for preparing ultrahigh-pressure compacted lithium iron phosphate positive electrode materials and a lithium ion battery. Background Art

[0002] At present, the methods used to improve the compaction density of lithium iron phosphate materials are mainly the following methods: 1. Increase the particle size of primary particles; 2. Reduce the carbon content; 3. Reduce the porosity; 4. Improve the coated carbon source; 5. Improve the gradation between particles; 6. Improve the smoothness of the material surface, etc. The easiest choice is to increase the particle size of the primary particles, and then use a smaller particle size to fill the gaps between the large particle sizes, so as to achieve graded stacking. However, the defects of this method are also obvious. Compared with nano-sized particles, the solid lithium iron phosphate particles with large particle sizes still have a long electron conduction and lithium transport distance, and the electrolyte is difficult to penetrate into the solid particles, which limits the performance of the solid particles. Therefore, the hollow microsphere lithium iron phosphate particles and lithium iron phosphate nanoparticles innovatively adopted in this application are compounded to achieve graded stacking, and metal doping is not used for filling. It can not only avoid the problems of solid particles, but also solve the problem of uneven dispersion of lithium iron phosphate caused by metal doping, and this method can also effectively improve the compaction degree. Summary of the invention

[0003] The purpose of the present invention is to provide a method for preparing an ultra-high-density lithium iron phosphate positive electrode material and a lithium ion battery to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: The method for preparing ultra-high-pressure compacted lithium iron phosphate positive electrode material comprises the following preparation steps: S1. According to a mass ratio of 1:45-50, add 80-85% phosphoric acid to the polyethylene glycol solution, stir evenly, and prepare solution A for standby; according to a mass ratio of 1:70-75, add lithium hydroxide to the polyethylene glycol solution, stir evenly, and then add solution A with a mass of 75-80 times of lithium hydroxide, stir for 30-35 minutes, vacuum filter, and wash the filtered product with deionized water and anhydrous ethanol for 3-5 times respectively, and then vacuum dry at a temperature of 95-105°C for 3-4 hours to obtain a hollow microsphere template; S2. Add ferrous sulfate heptahydrate and hollow microsphere template to ethylene glycol with a mass ratio of 4.8-5.2 times that of ferrous sulfate heptahydrate in a mass ratio of 4.8-5:1, stir for 15-20 minutes, gradually heat to 150°C in an argon atmosphere, react for 3-3.5 hours, add L-ascorbic acid with a mass of 0.1-0.08 times that of ferrous sulfate heptahydrate, stir evenly, add the precursor mixture, stir for 30-35 minutes, heat to 180°C in an argon atmosphere after stirring, continue to react for 16-18 hours, cool to 25-35°C after the reaction, filter the lower precipitate, and remove the filtered product with a deionized water. The precursor mixture comprises the following steps: weighing lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.7-0.9, adding lithium hydroxide monohydrate to ethylene glycol with a mass of 35-45 times that of lithium hydroxide monohydrate, stirring and dissolving, and then adding graphene dispersion with a mass of 1.1-1.3 times that of ethylene glycol, stirring evenly, and preparing a precursor mixture for standby use; wherein the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid is 3.2-3.5:3:1; S3. Mix the composite and the carbon source in a mass ratio of 8-10:1, stir for 1-1.5 hours, and then dry at 45-50°C for 24-26 hours. After drying, perform a two-step calcination treatment in an argon atmosphere. After calcination, cool to 25-35°C to obtain a lithium iron phosphate positive electrode material.

[0005] As an optimization, the graphene dispersion includes the following preparation steps: adding graphene oxide to ethylene glycol with a mass of 900 to 950 times that of graphene oxide, stirring evenly and then ultrasonically dispersing for 30 to 40 minutes for use.

[0006] As an optimization, the graphene oxide includes the following preparation steps: weighing flake graphite and sodium nitrate according to a mass ratio of 1:0.5-0.6, adding flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 40-45 times the mass of flake graphite, ultrasonicating for 30-35 minutes at a temperature of -5-0°C, adding potassium permanganate with a mass fraction of 2.8-3 times the mass of flake graphite after ultrasonication, stirring for 2-2.5 hours at a temperature of 0-5°C, and then ultrasonicating for 30-35 minutes at a temperature of 30-35°C, and then adding 95% of the mass of flake graphite. ~100 times of deionized water, then stirred for 30~35min at a temperature of 90~95℃, then added deionized water 55~60 times of the mass of the flake graphite, after standing for 20~30min, added hydrogen peroxide 30~32 times of the mass of the flake graphite with a mass fraction of 30~35%, after standing for 15~20min, added hydrochloric acid solution 45~50 times of the mass of the flake graphite with a mass fraction of 10~15%, after standing for stratification, took out the lower precipitate, washed with deionized water 3~5 times, centrifuged and washed the precipitate until neutral, to obtain graphene oxide.

[0007] As an optimization, the two-step calcination treatment includes the following preparation steps: calcination at a temperature of 330-350°C for 2-2.2 hours, and then calcination at a temperature of 690-700°C for 4-10.2 hours.

[0008] As an optimization, the heating and cooling rates during the two-step calcination treatment are both 5°C / min.

[0009] As an optimization, the carbon source is sucrose.

[0010] A lithium iron phosphate positive electrode material prepared by any of the above methods for preparing ultra-high-pressure compacted lithium iron phosphate positive electrode materials.

[0011] A method for preparing an ultra-high-density lithium iron phosphate positive electrode material as described in any one of the above and its application in a lithium-ion battery.

[0012] Compared with the prior art, the beneficial effects achieved by the present invention are: The present application adopts the method of first synthesizing a lithium phosphate hollow microsphere template using phosphoric acid and lithium hydroxide as a phosphorus source and a lithium source respectively, then synthesizing a hollow lithium iron phosphate microsphere by a solvothermal method using ferrous sulfate heptahydrate and a lithium phosphate hollow microsphere template, and then directly continuing the reaction to generate nano-scale lithium iron phosphate particles on this basis, and in-situ composite graphene is performed while generating the nano-scale lithium iron phosphate particles, so that the hollow lithium iron phosphate microspheres and the nano-scale lithium iron phosphate particles are more evenly dispersed, and graphene doping is completed, and graphene is used as a conductive additive, and sucrose is further used as a surface carbon coating modification, so as to construct an efficient conductive network in which graphene doping and carbon coating work synergistically, solve the interface obstruction and point contact effect of electron transmission, so that electrons can be efficiently transmitted, thereby improving the electrochemical properties of the material; In the process of replacing the hollow microsphere template with ferrous sulfate heptahydrate, the reaction occurs from the surface of the particle and gradually reacts to the inside of the particle. Along with the exchange process of iron ions and lithium ions from the outside to the inside of the particle, the volume of the outer layer of the particle expands, and at the same time, the hollow microsphere template inside is continuously consumed, and the particle gradually presents a hollow structure. Finally, when the reaction is completed, a lithium iron phosphate microsphere material with a hollow structure is formed; the hollow structure can effectively avoid the long electron conduction and lithium ion transport distance inside the particle, and the electrolyte can easily penetrate into the interior of the particle, so that its performance can be fully exerted, the side reaction between the electrode material and the electrolyte is reduced, and the packing density is increased; after the replacement is completed, L-ascorbic acid is added to change the pH of the reaction material to end the replacement reaction and promote the reaction to a coprecipitation process. DETAILED DESCRIPTION

[0013] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0014] Example 1

[0015] A1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.5, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 40 times the mass of flake graphite, and ultrasonicate for 30 minutes at a temperature of -5°C. After ultrasonication, add potassium permanganate with a mass fraction of 2.8 times the mass of flake graphite, and then stir for 2 hours at a temperature of 0°C. After ultrasonication for 30 minutes at a temperature of 30°C, add deionized water with a mass fraction of 95 times the mass of flake graphite, and then stir for 30 minutes at a temperature of 90°C. Then, add deionized water 55 times the mass of the flake graphite, let it stand for 20 minutes, then add 30% hydrogen peroxide 30 times the mass of the flake graphite, let it stand for 15 minutes, then add 10% hydrochloric acid solution 45 times the mass of the flake graphite, let it stand for stratification, take out the lower layer of precipitation, wash it with deionized water 3 times, centrifuge and wash it to neutrality to obtain graphene oxide; add the graphene oxide to ethylene glycol 900 times the mass of the graphene oxide, stir evenly, and then ultrasonically disperse it for 30 minutes for standby use; A2. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.7, add lithium hydroxide monohydrate to ethylene glycol with a mass of 35 times that of lithium hydroxide monohydrate, stir to dissolve, then add graphene dispersion with a mass of 1.1 times that of ethylene glycol, stir evenly, and prepare a precursor mixture for use; A3. According to a mass ratio of 1:45, add 80% phosphoric acid to the polyethylene glycol solution, stir evenly, and prepare solution A for standby; according to a mass ratio of 1:70, add lithium hydroxide to the polyethylene glycol solution, stir evenly, and then add solution A with a mass of 75 times that of lithium hydroxide. After stirring for 30 minutes, vacuum filter and wash the filtered product with deionized water and anhydrous ethanol for 3 times respectively, and then vacuum dry at 95°C for 3 hours to obtain a hollow microsphere template; A4. According to the mass ratio of 4.8:1, ferrous sulfate heptahydrate and hollow microsphere template were added to ethylene glycol with a mass of 4.8 times that of ferrous sulfate heptahydrate, stirred for 15 minutes, and then gradually heated to 150°C in an argon atmosphere. After reacting for 3 hours, L-ascorbic acid with a mass of 0.08 times that of ferrous sulfate heptahydrate was added, stirred evenly, and then added to the precursor mixture, stirred for 30 minutes. After the stirring was completed, the temperature was raised to 180°C in an argon atmosphere, and the reaction was continued for 16 hours. After the reaction was completed, it was cooled to 25°C, and the lower precipitate was filtered, and the filtered product was washed with deionized water and anhydrous ethanol for 3 times respectively. After washing, it was dried at 45°C for 24 hours to obtain a composite; the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid was 3.2:3:1; A5. The composite and sucrose were mixed in a mass ratio of 8:1, stirred for 1 hour, and then dried at 45°C for 24 hours. After drying, they were calcined in two steps under an argon atmosphere. After calcination, they were cooled to 25°C to obtain a lithium iron phosphate positive electrode material. The two-step calcination process included the following preparation steps: calcination at 330°C for 2 hours, and then calcination at 690°C for 4 hours. The heating and cooling rates during the two-step calcination process were both 5°C / min.

[0016] Example 2

[0017] A1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.55, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid (42.5 times the mass of flake graphite), ultrasonicate for 32.5 min at -2.5°C, add potassium permanganate (2.9 times the mass of flake graphite) after ultrasonication, stir for 2.25 h at 2.5°C, ultrasonicate for 32.5 min at 32.5°C, add deionized water (97.5 times the mass of flake graphite), and stir for 32 h at 92.5°C. .5min, then add deionized water 57.5 times the mass of the flake graphite, let it stand for 25min, then add hydrogen peroxide 32.5% by mass 31 times the mass of the flake graphite, let it stand for 17.5min, then add hydrochloric acid solution 12.5% ​​by mass 47.5 times the mass of the flake graphite, let it stand for stratification, take the lower precipitate, wash it with deionized water 4 times, centrifuge and wash it to neutrality to obtain graphene oxide; add graphene oxide to ethylene glycol 925 times the mass of graphene oxide, stir evenly, and then ultrasonically disperse for 35min for use; A2. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.8, add lithium hydroxide monohydrate to ethylene glycol with a mass that is 40 times that of lithium hydroxide monohydrate, stir to dissolve, then add graphene dispersion with a mass that is 1.2 times that of ethylene glycol, stir evenly, and prepare a precursor mixture for use; A3. According to the mass ratio of 1:47.5, add 82.5% phosphoric acid to the polyethylene glycol solution, stir evenly, and prepare solution A for standby; according to the mass ratio of 1:72.5, add lithium hydroxide to the polyethylene glycol solution, stir evenly, and then add solution A with 77.5 times the mass of lithium hydroxide, stir for 32.5 minutes, vacuum filter, and wash the filtered product with deionized water and anhydrous ethanol for 4 times respectively, and then vacuum dry for 3.5 hours at 100°C to obtain a hollow microsphere template; A4. According to the mass ratio of 4.9:1, ferrous sulfate heptahydrate and hollow microsphere template were added to ethylene glycol with a mass of 5 times that of ferrous sulfate heptahydrate, stirred for 17.5 minutes, and then gradually heated to 150°C in an argon atmosphere. After reacting for 3.25 hours, L-ascorbic acid with a mass of 0.09 times that of ferrous sulfate heptahydrate was added, stirred evenly, and then added to the precursor mixture, stirred for 32.5 minutes. After the stirring was completed, the temperature was raised to 180°C in an argon atmosphere, and the reaction was continued for 17 hours. After the reaction was completed, it was cooled to 30°C, and the lower precipitate was filtered, and the filtered product was washed with deionized water and anhydrous ethanol for 4 times respectively. After washing, it was dried at a temperature of 47.5°C for 25 hours to obtain a composite; the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid was 3.35:3:1; A5. The composite and sucrose were mixed in a mass ratio of 9:1, stirred for 1.25 h, and then dried at 47.5 °C for 25 h. After drying, they were calcined in two steps under an argon atmosphere. After calcination, they were cooled to 30 °C to obtain a lithium iron phosphate positive electrode material. The two-step calcination process included the following preparation steps: calcination at 340 °C for 2.1 h, and then calcination at 695 °C for 4.1 h. The heating and cooling rates during the two-step calcination process were both 5 °C / min.

[0018] Example 3

[0019] A1. Weigh flake graphite and sodium nitrate in a mass ratio of 1:0.6, add flake graphite and sodium nitrate to 98% concentrated sulfuric acid with a mass fraction of 45 times the mass of flake graphite, and perform ultrasonic treatment at 0°C for 35 minutes. After the ultrasonic treatment, add potassium permanganate with a mass fraction of 3 times the mass of flake graphite, and then stir at 5°C for 2.5 hours. After that, perform ultrasonic treatment at 35°C for 35 minutes, add deionized water with a mass fraction of 100 times the mass of flake graphite, and then stir at 95°C for 35 minutes. Then, add deionized water 60 times the mass of the flake graphite, let it stand for 30 minutes, then add 35% hydrogen peroxide 32 times the mass of the flake graphite, let it stand for 20 minutes, then add 15% hydrochloric acid solution 50 times the mass of the flake graphite, let it stand for stratification, take the lower precipitate, wash it with deionized water 5 times, centrifuge and wash it to neutrality to obtain graphene oxide; add the graphene oxide to ethylene glycol 950 times the mass of the graphene oxide, stir evenly, and then ultrasonically disperse it for 40 minutes for standby use; A2. Weigh lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.9, add lithium hydroxide monohydrate to ethylene glycol with a mass of 45 times that of lithium hydroxide monohydrate, stir to dissolve, then add graphene dispersion with a mass of 1.3 times that of ethylene glycol, stir evenly, and prepare a precursor mixture for use; A3. According to a mass ratio of 1:50, add 85% phosphoric acid to the polyethylene glycol solution, stir evenly, and prepare solution A for standby; according to a mass ratio of 1:75, add lithium hydroxide to the polyethylene glycol solution, stir evenly, and then add solution A with a mass of 80 times that of lithium hydroxide. After stirring for 35 minutes, vacuum filter and wash the filtered product with deionized water and anhydrous ethanol for 5 times respectively, and then vacuum dry at a temperature of 105°C for 4 hours to obtain a hollow microsphere template; A4. According to the mass ratio of 5:1, ferrous sulfate heptahydrate and hollow microsphere template were added to ethylene glycol with a mass of 5.2 times that of ferrous sulfate heptahydrate, stirred for 20 minutes, and then gradually heated to 150°C under an argon atmosphere. After reacting for 3.5 hours, L-ascorbic acid with a mass of 0.1 times that of ferrous sulfate heptahydrate was added, stirred evenly, and then added to the precursor mixture, stirred for 35 minutes. After the stirring was completed, the temperature was raised to 180°C under an argon atmosphere, and the reaction was continued for 18 hours. After the reaction was completed, it was cooled to 35°C, and the lower precipitate was filtered, and the filtered product was washed with deionized water and anhydrous ethanol for 5 times respectively. After washing, it was dried at a temperature of 50°C for 26 hours to obtain a composite; the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid was 3.5:3:1; A5. The composite and sucrose were mixed in a mass ratio of 10:1, stirred for 1.5 h, and then dried at 50 °C for 26 h. After drying, two-step calcination was performed in an argon atmosphere. After calcination, the mixture was cooled to 35 °C to obtain a lithium iron phosphate positive electrode material. The two-step calcination process included the following preparation steps: calcination at 350 °C for 2.2 h, and then calcination at 700 °C for 4.2 h. The heating and cooling rates during the two-step calcination process were both 5 °C / min.

[0020] Example 4

[0021] The only difference from Example 2 is step A4: ferrous sulfate heptahydrate and the hollow microsphere template are added to ethylene glycol with a mass ratio of 5:1, and stirred for 20 minutes. Then, the temperature is gradually raised to 150°C under an argon atmosphere. After reacting for 3.5 hours, the mixture is cooled to 35°C, the lower precipitate is filtered, and the filtered product is washed 5 times with deionized water and anhydrous ethanol respectively. After washing, it is dried at 50°C for 26 hours to obtain a composite.

[0022] Example 5

[0023] The only difference from Example 2 is step A4: adding ferrous sulfate heptahydrate to ethylene glycol with a mass of 5.2 times that of ferrous sulfate heptahydrate, stirring for 20 minutes, gradually heating to 150°C under an argon atmosphere, reacting for 3.5 hours, adding L-ascorbic acid with a mass of 0.1 times that of ferrous sulfate heptahydrate, stirring evenly, adding the precursor mixture, stirring for 35 minutes, heating to 180°C under an argon atmosphere after the stirring is completed, continuing to react for 18 hours, cooling to 35°C after the reaction is completed, filtering the lower precipitate, and washing the filtered product with deionized water and anhydrous ethanol for 5 times respectively, and drying at 50°C for 26 hours after washing to obtain a composite; the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid is 1:3:1; Mechanical properties and aging resistance tests: Pole performance test Pole piece parameter measurement: Select the pole pieces after coating, pressing, 24 hours after pressing, and extreme pressing. Use an electronic balance to accurately weigh the pole piece weight to obtain the pole piece surface density. Then, use a micrometer to measure the pole piece thickness, and collect 10 thickness data for each pole piece.

[0024] Pole sheet compaction density = pole sheet surface density / (pole sheet thickness - current collector thickness).

[0025] Performance evaluation under special charge and discharge regime: In the CT2001A model Lanqi charging cabinet, a special charge and discharge regime is used to evaluate the battery performance. Due to the influence of thermodynamic factors, the battery discharge capacity may exceed 100%.

[0026] The specific evaluation method is as follows: 5C rate discharge performance evaluation: The battery is first charged to 3.8V at a constant current of 1C, and then discharged to 2.0V at a constant current of 5C to evaluate the performance of the battery at a 5C rate discharge.

[0027] 2C rate charging performance evaluation: The battery is charged to 3.8V at a constant current of 2C, and then discharged to 2.0V at a constant current of 1C to evaluate the performance of the battery when charged at a 2C rate.

[0028] 1C cycle performance test: The battery is charged and discharged 1000 times by 1C constant current charging to 3.8V and 1C constant current discharging to 2.0V, and the capacity retention rate of the battery after 1000 cycles is calculated.

[0029] Table 1 Mechanical properties and aging resistance test results Sample <![CDATA[Pole piece compaction density / (g / cm 3 )]]> 5C rate discharge / % 2C rate charging / % Cycle performance / % Example 1 2.79 100 101 95 Example 2 2.72 98 100 98 Example 3 2.73 97 100 97 Example 4 2.33 87 89 88 Example 5 2.12 76 79 79 From the comparison of the experimental data of Examples 1 to 3 in Table 1, it can be found that the lithium iron phosphate particle electrode prepared by the present invention has an ultra-high compaction density and a discharge cycle performance of more than 100%; In Example 4, since only hollow microspheres are used as lithium iron phosphate particles, they have a large porosity, resulting in poor final performance. In Example 5, nanoparticles are used as the filling body, and their compaction density is significantly reduced, resulting in a decrease in final performance.

[0030] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing an ultra-high-density lithium iron phosphate positive electrode material, characterized in that: The method comprises the following preparation steps: S1. According to a mass ratio of 1:45-50, add 80-85% phosphoric acid to the polyethylene glycol solution, stir evenly, and prepare solution A for standby; according to a mass ratio of 1:70-75, add lithium hydroxide to the polyethylene glycol solution, stir evenly, and then add solution A with a mass of 75-80 times of lithium hydroxide, stir for 30-35 minutes, vacuum filter, and wash the filtered product with deionized water and anhydrous ethanol for 3-5 times respectively, and then vacuum dry at a temperature of 95-105°C for 3-4 hours to obtain a hollow microsphere template; S2. Add ferrous sulfate heptahydrate and hollow microsphere template to ethylene glycol with a mass ratio of 4.8-5.2 times that of ferrous sulfate heptahydrate in a mass ratio of 4.8-5:1, stir for 15-20 minutes, gradually heat to 150°C in an argon atmosphere, react for 3-3.5 hours, add L-ascorbic acid with a mass of 0.1-0.08 times that of ferrous sulfate heptahydrate, stir evenly, add the precursor mixture, stir for 30-35 minutes, heat to 180°C in an argon atmosphere after stirring, continue to react for 16-18 hours, cool to 25-35°C after the reaction, filter the lower precipitate, and remove the filtered product with a deionized water. The precursor mixture comprises the following steps: weighing lithium hydroxide monohydrate and phosphoric acid in a mass ratio of 1:0.7-0.9, adding lithium hydroxide monohydrate to ethylene glycol with a mass of 35-45 times that of lithium hydroxide monohydrate, stirring and dissolving, and then adding graphene dispersion with a mass of 1.1-1.3 times that of ethylene glycol, stirring evenly, and preparing a precursor mixture for standby use; wherein the molar ratio of ferrous sulfate heptahydrate, lithium hydroxide monohydrate and phosphoric acid is 3.2-3.5:3:1; S3. Mix the composite and the carbon source in a mass ratio of 8-10:1, stir for 1-1.5 hours, and then dry at 45-50°C for 24-26 hours. After drying, perform a two-step calcination treatment in an argon atmosphere. After calcination, cool to 25-35°C to obtain a lithium iron phosphate positive electrode material.

2. The method for preparing the ultra-high compacted lithium iron phosphate positive electrode material according to claim 1, characterized in that: The graphene dispersion comprises the following preparation steps: adding graphene oxide to ethylene glycol with a mass of 900 to 950 times that of graphene oxide, stirring evenly, and then ultrasonically dispersing for 30 to 40 minutes for standby use.

3. The method for preparing the ultra-high compacted lithium iron phosphate positive electrode material according to claim 2, characterized in that: The graphene oxide comprises the following preparation steps: weighing flake graphite and sodium nitrate in a mass ratio of 1:0.5-0.6, adding the flake graphite and sodium nitrate into 98% concentrated sulfuric acid with a mass fraction of 40-45 times the mass of the flake graphite, ultrasonicating for 30-35 minutes at a temperature of -5-0°C, adding potassium permanganate with a mass fraction of 2.8-3 times the mass of the flake graphite after the ultrasonication, stirring for 2-2.5 hours at a temperature of 0-5°C, ultrasonicating for 30-35 minutes at a temperature of 30-35°C, and then adding 95-10% of the mass of the flake graphite. 0 times of deionized water, then stirred for 30-35 minutes at a temperature of 90-95°C, then added 55-60 times of deionized water as the mass of the flake graphite, allowed to stand for 20-30 minutes, then added 30-32 times of the mass of the flake graphite with a mass fraction of 30-35% hydrogen peroxide, allowed to stand for 15-20 minutes, then added 45-50 times of the mass of the flake graphite with a mass fraction of 10-15% hydrochloric acid solution, allowed to stand for stratification, removed the lower precipitate, washed with deionized water for 3-5 times, centrifuged and washed the precipitate until neutral, to obtain graphene oxide.

4. The method for preparing the ultra-high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The two-step calcination treatment includes the following preparation steps: calcining at a temperature of 330-350° C. for 2-2.2 hours, and then calcining at a temperature of 690-700° C. for 4-10.2 hours.

5. The method for preparing the ultra-high-density lithium iron phosphate positive electrode material according to claim 1, characterized in that: The heating and cooling rates during the two-step calcination treatment were both 5°C / min.

6. The method for preparing the ultra-high compacted lithium iron phosphate positive electrode material according to claim 1, characterized in that: The carbon source is sucrose.

7. A lithium iron phosphate positive electrode material prepared by the method for preparing an ultra-high-density lithium iron phosphate positive electrode material as claimed in any one of claims 1 to 6.

8. Use of the method for preparing the ultra-high-density lithium iron phosphate positive electrode material according to any one of claims 1 to 6 in a lithium-ion battery.

Citation Information

Patent Citations

  • Lithium iron phosphate composite material, production method and use thereof

    CN103003193A

  • Iron phosphate, lithium iron phosphate as well as preparation methods of iron phosphate and lithium iron phosphate

    CN103887499A

  • Preparation method of micro-nano porous structure ferric phosphate precursor and lithium ferric phosphate positive electrode material by means of two steps co-precipitation

    CN106876700A

  • Preparation method of carbon-coated lithium iron phosphate hollow nanospheres

    CN107507975A

  • Preparation method of positive electrode material for graphene lithium iron phosphate vanadium oxide batteries

    CN108039474A